2016
DOI: 10.1002/eqe.2795
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of resettable energy dissipating devices in seismic response modification of elastic SDoF systems

Abstract: Summary Semi‐active variable stiffness resettable devices can reduce seismic demands and damages in structures. Despite their advantages, variable stiffness resettable devices are under‐utilized mainly because of the shortage of fundamental research in quantifying the sensitivity of key seismic response parameters, and losses, in structures that use such systems for seismic hazard mitigation. Within this setting, the research summarized herein measures the effectiveness of semi‐active resettable energy dissipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…The device is used to vary or increase the stiffness of the system in real‐time. Fardadi et al 20 . investigated the seismic response of a SDOF system using a SRS whereby the stiffness is added through a bracing system, shown in Figure 1.…”
Section: Characteristics Of Srsmentioning
confidence: 99%
See 3 more Smart Citations
“…The device is used to vary or increase the stiffness of the system in real‐time. Fardadi et al 20 . investigated the seismic response of a SDOF system using a SRS whereby the stiffness is added through a bracing system, shown in Figure 1.…”
Section: Characteristics Of Srsmentioning
confidence: 99%
“…Three control laws were implemented in prior work, 20 denoted as 1‐4, 1&3, and 2&4, referring to the active quadrant of the figure representing the bracing system's load‐displacement curve. From the three control laws, it was found that control law 1‐4 was most effective in reducing the displacement of the frame.…”
Section: Characteristics Of Srsmentioning
confidence: 99%
See 2 more Smart Citations